Engenharia Cartográfica e de Agrimensura: história, estrutura e perspectivas futuras - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The human race has always sought ways to represent the space where it is inserted, and two areas the Surveying and Cartography arose to help in the development of this representation, with techniques and equipment that over the years are improved and developed as sciences for studies thus creating the courses of Engineering Surveying and Cartographic Engineering that in Brazil. With the objective of presenting the courses of Engineering Survey and Cartographic Engineering through documents, to analyze the proposal of unification between them and to show their occupation in the labor market and their attributions before the council where the future professional is inserted, that corroborate for their unification, done through a documentary research of the development of the courses in Brazil by means of: Sites; Books and Laws. Besides of trying to understand which are the knowledge of students who are finishing the high school about these areas and their future perspectives in higher education, presenting the course of Cartographic and Surveying Engineering of UNIPAMPA as a possible place of formation in this area. By means of a study made with 106 institutions of high school and technical education of Rio Grande do Sul that are within UNIPAMPA's area of influence published and made available online in the form of a questionnaire.
Cartographic and Surveying Engineering: history, structure and future perspectives
Keywords: Agrimensura; Cartografia; Engenharia de Agrimensura; Engenharia Cartográfica; UNIPAMPA; Surveying; Cartography; Surveying Engineering; Cartographic Engineering; CNPQ::ENGENHARIAS